PASTORALISTS’ PERCEPTIONS ON AN INVASIVE ALIEN PLANT PARTHENIUM HYSTEROPHORUS AND ITS MANAGEMENT CONTROL IN SIMANJIRO DISTRICT, TANZANIA - Musese, Leticia J.; Shirima, Deo D.; Kilewa, Ramadhan (International Journal of Research -GRANTHAALAYAH, 2020)
The Maasai pastoralist community resides in Simanjiro District, Manyara Region, Tanzania. As a pastoralist community they are largely dependent on rangelands as a source of forage for their livestock. However, plant invasions are threatening rangeland productivity, displacing valuable forage species, leading to a reduction in livestock populations. The noxious weed Parthenium hysterophorus has recently been established in Simanjiro District and may pose a significant threat to livelihoods if effective control strategies are not put in place. This study was therefore conducted to determine pastoralists’ understanding of P. hysterophorus in Simanjiro District, Tanzania. Semi-structured and open-ended questionnaires were used to collect information on, among others, the date of introduction, means of spread, area coverage, effects of P. hysterophorus on livestock health and management control for P. hysterophorus. Pastoralists were unaware of when P. hysterophorus was introduced although they mentioned vehicles, people and livestock to be the main vectors of introduction and spread. They confirmed that P. hysterophorus has little/some expanding its range since it was first noticed at the beginning of this decade. Furthermore, most pastoralists were not aware of the effects of Parthenium weed in livestock although few reported it causing distasteful and less milk and diarrhoea after consuming the weed. There were no major efforts in place to control Parthenium weed. Therefore, efforts need to be made to motivate pastoralists through community awareness campaigns to impart knowledge on how to control P. hysterophorus to promote rangeland productivity. Also, community awareness the impacts of the weed on their livestock and human health.